Evaluating component importance and reliability of power transmission networks subject to windstorms: methodology and application to the nordic grid - Scherb, Anke; Garrè, Luca; Straub, Daniel (Reliability engineering & system safety, 2019)
•Most important lines are identified through various component rankings.•Lines that are important for the initialization of network damage do not correspond to lines that are responsible for the further propagation of damages.•By improving the identified most important components, the overall network reliability can be enhanced by up to 50%. We present a procedure for the efficient assessment of component importance and network reliability in power transmission grids subject to wind hazards. A stochastic wind load model is learned from windstorm data. Component fragility models are established by combining information on the design wind loads prescribed by the relevant structural codes and the observed failure rate in the network as a whole. Network performance is assessed by a DC power flow model, which accounts for cascading failures and potential islanding due to load redistribution after initial failure events caused by the windstorms. Besides evaluating the network reliability, selected importance measures are defined to rank single components according to their influence on the overall system reliability. We thereby distinguish component importance related to initial failures triggered by the windstorms and component importance related to potential subsequent cascading failures. The procedure is demonstrated by application to the Nordic Grid model of the electrical power transmission network in Denmark, Norway, Sweden, and Finland. We find that the procedure can provide an efficient basis for planning network improvements in terms of (1) strengthening vulnerable line segments against wind loads and (2) increasing line capacities to limit cascading failures.